Calycosin-7-O-β-D-glucoside Attenuates OGD/R-Induced Damage by Preventing Oxidative Stress and Neuronal Apoptosis via the SIRT1/FOXO1/PGC-1α Pathway in HT22 Cells. (1st December 2019) - Yan, Xiangli; Yu, Aiming; Zheng, Haozhen; Wang, Shengxin; He, Yingying; Wang, Lisheng
Abstract : Neuronal apoptosis induced by oxidative stress is a major pathological process that occurs after cerebral ischemia-reperfusion. Calycosin-7- O - β - D -glucoside (CG) is a representative component of isoflavones in Radix Astragali (RA). Previous studies have shown that CG has potential neuroprotective effects. However, whether CG alleviates neuronal apoptosis through antioxidant stress after ischemia-reperfusion remains unknown. To investigate the positive effects of CG on oxidative stress and apoptosis of neurons, we simulated the ischemia-reperfusion process in vitro using an immortalized hippocampal neuron cell line (HT22) and oxygen-glucose deprivation/reperfusion (OGD/R) model. CG significantly improved cell viability and reduced oxidative stress and neuronal apoptosis. In addition, CG treatment upregulated the expression of SIRT1, FOXO1, PGC-1 α, and Bcl-2 and downregulated the expression of Bax. In summary, our findings indicate that CG alleviates OGD/R-induced damage via the SIRT1/FOXO1/PGC-1 α signaling pathway. Thus, CG maybe a promising therapeutic candidate for brain injury associated with ischemic stroke.